2010
DOI: 10.1002/jrs.2850
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectroscopy in art and archaeology

Abstract: Paris (2005) [3] and Modena (2007). [4] The scientific programme included all applications and studies performed with Raman spectroscopy on Cultural Heritage and related materials. The conference offered an outstanding and unique opportunity for exchanging knowledge on leading edge developments. Cultural Heritage studies, interpreted in a broad sense, included amongst others,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 26 publications
(25 reference statements)
0
34
0
Order By: Relevance
“…The use of Raman spectroscopy for archaeometry applications has quickly grown in the last years, in both micro‐Raman and mobile Raman versions of the technique, thanks to the main advantages as the small time required for the measurements, the possibility to study untreated raw material and, especially, the noninvasivity. This tendency is indicated by the increasing number of dedicated conferences, as the International Conference in Application of Raman Spectroscopy in Art and Archaeology (RAA), now arrived at the 8th edition: many examples of interesting applications are reported in the RAA conference special issues . Some good review articles show the progression in the recent years of the state‐of‐the art of the use of Raman spectroscopy in different fields of archaeometry.…”
Section: Introductionmentioning
confidence: 99%
“…The use of Raman spectroscopy for archaeometry applications has quickly grown in the last years, in both micro‐Raman and mobile Raman versions of the technique, thanks to the main advantages as the small time required for the measurements, the possibility to study untreated raw material and, especially, the noninvasivity. This tendency is indicated by the increasing number of dedicated conferences, as the International Conference in Application of Raman Spectroscopy in Art and Archaeology (RAA), now arrived at the 8th edition: many examples of interesting applications are reported in the RAA conference special issues . Some good review articles show the progression in the recent years of the state‐of‐the art of the use of Raman spectroscopy in different fields of archaeometry.…”
Section: Introductionmentioning
confidence: 99%
“…Several reviews and comprehensive articles including discussions of state of the art instrumentation and of the advantages and limitations of Raman spectroscopy for the analysis of pigments and some of their degradation products in works of art and in archaeological artifacts, as well as of studies aimed to shed light onto pigment manufacturing technology, have been published . Snapshots of the evolution of the technique in innovative applications to the study of the complex and diverse materials found in objects of cultural significance can also be found in the papers presented at the biennial Raman Spectroscopy in Art and Archaeology meetings, the first of which took place at the British Museum in 2001, published by The Royal Society of Chemistry and by the Journal of Raman Spectroscopy …”
Section: Introductionmentioning
confidence: 99%
“…Other IR and Raman spectral libraries of pigments and minerals are also available in literature and internet [15,77,78]. Abundant case studies focused on the application of FTIR and Raman spectroscopy to the analysis of pigments can be found in literature [15,79]. In particular, the series of monographs on artists' pigments edited by the National Gallery of Washington provides abundant analytical IR and Raman data on historical pigments [58][59][60][61].…”
Section: Spectral Features Of Pigmentsmentioning
confidence: 99%